A modified suture technique for peripheral arterial cardiopulmonary bypass - Ata, Emin Can; Erkanlı, Korhan (Turkish National Vascular and Endovascular Surgery Society, 2020)
Peripheral cannulation for cardiopulmonary bypass is a frequently used technique in minimally invasive cardiac surgery and reoperation. In patients with a small arterial caliber, the purse suture on the femoral artery leads to marked stenosis after decannulation. In order to prevent this condition, we used double parallel U-sutures rather than purse sutures for arterial cannulation. Herein, we present this technique in the light of literature data.
Keywords: Cardiopulmonary Bypass; Peripheral Cannulation; Suture